2014
DOI: 10.5539/elt.v7n6p87
|View full text |Cite
|
Sign up to set email alerts
|

Emirati and Saudi Students’ Writing Challenges at U.S. Universities

Abstract: The study examines writing challenges Emirati and Saudi students face at U.S. universities. Based on a sample of 219, a mixed methods approach was used to analyze responses from the participants. The results of the questionnaire reveal that Less than 31% Emirati and Saudi students feel "comfortable" in completing written assignments. The interviews results indicate that Emirati and Saudi students have different opinions regarding writing difficulties. An Emirati student, stated: "I am worried a lot because wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Regarding writing, Al Murshidi (2014) reported that Saudi students need more coursework in academic writing to prepare them for their future disciplines. Al-Khairy (2013b) recommended that faculty give students intensive practice in writing paragraphs of reasonable length.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding writing, Al Murshidi (2014) reported that Saudi students need more coursework in academic writing to prepare them for their future disciplines. Al-Khairy (2013b) recommended that faculty give students intensive practice in writing paragraphs of reasonable length.…”
Section: Discussionmentioning
confidence: 99%
“…Saudi EFL learners seem to suffer from the same difficulty. Many studies examined the problem of vocabulary deficiency in EFL Saudi learners (e.g., Al-Khairy, 2013;Al-Murshidi, 2014;Al-Qahtani, 2016;Al-Rabai, 2016;Al-Saif & Milton, 2012;Hamouda, 2013;Khan, 2016;Milton, 2012;Rafada & Madini, 2017). In order to find out how serious the problem was, a vocabulary test was administered to a group of EFL students at Jubail College of Education, IAU University.…”
Section: Problem Of the Studymentioning
confidence: 99%
“…Undeniably, higher students in the non-English country tend to have particular difficulties in English writing. In higher education research, there are several contexts considering difficult in writing process, which represent literacy perspective, knowledge, technical aspect of writing, characteristics of language and the difference of linguistic and cultural background (Lea and Street as cited in Murshidi, 2014). Moreover, Phothongsunan (2016) claimed that difficulties faced by Thai University Academics" are classified into three types: (1) discursive challenges, non-discursive challenges, and (3) other challenges.…”
Section: Introductionmentioning
confidence: 99%